Biomarker techniques to screen for bacteria that produce polyunsaturated fatty acids - David Nichols; Thomas McMeekin (2002)
The production of polyunsaturated fatty acids (PUFA) by bacteria has been firmly established for over two decades although it is still commonly ignored. Investigations of Antarctic sea ice have revealed a high diversity of novel bacterial taxa with the ability to produce PUFA. The majority are psychrophilic (requiring low temperatures for growth) and halophilic (requiring the presence of salts for growth), in contrast to the bacterial community present in the underlying water column. Specific fatty acids may be used as indicators of PUFA-producing bacteria in environmental samples. Structural studies of bacterial phospholipids have been particularly revealing in suggesting biomarkers specific for prokaryotic PUFA input. The use of negative ion fast atom bombardment tandem mass spectrometry for the analysis of bacterial phospholipids has identified species specific for certain groups of bacterial PUFA producers. The phylogeny of PUFA production in the Î³-Proteobacteria also suggests the future use of PUFA genes for the assessment of marine bacterial biodiversity. Â© 2002 Elsevier Science B.V. All rights reserved.